Effect of solar temperature field on a sea-crossing cable-stayed bridge tower. Issue 8 (June 2019) - Li, Yuan; He, Shuanhai; Liu, Peng
Based on the transient temperature field theory of heat conduction, the solar temperature field calculation model of a sea-cross cable-stayed bridge tower was established and calculated through transient heat transfer analysis, with the largest sea-cross construction project of Kong–Zhuhai–Macao Bridge as an example. The main parameters, including the solar elevation angle, azimuth angle, radiation absorption coefficient, and length of overhang, were incorporated. The proposed model was verified by comparing the measured data with the predicted values of both the temperature field and temperature deformation. The analysis results and monitoring data achieved a good agreement, which reveals that integrating numerical analysis with field monitoring data can be utilized to thoroughly understand the effects of a solar temperature field on a sea-crossing cable-stayed bridge tower. The research results guide the construction of the bridge.